FRI0446 ATTAINMENT OF MINIMAL DISEASE ACTIVITY (MDA) IN PSORIATIC ARTHRITIS (PSA) PATIENTS (PTS) DEPENDING ON THE TIME OF SYNTHETIC (S) DMARDS INITIATION IN CLINICAL PRACTICE: RUSSIAN PSA REGISTRY (RU-PSART) DATA. (June 2019) - Loginova, Elena; Korotaeva, Tatiana; Koltakova, Anastasia; Gubar, Elena; Korsakova, Yulia; Sedunova, Maria; Pristavsky, Igor; Umnova, Irina; Bondareva, Irina; Kudishina, Snezana; Lila, Alexander
Abstract : Background: According to the EULAR recommendations and treat to target strategy sDMARD are the first line of PsA therapy. The goal of PsA treatment is attaining MDA. But there are contradictory data about the efficacy of sDMARDs in PsA pts. Data was collected from 25 rheumatology clinics of the Russian Federation. Objectives: To investigate the cumulative frequency and the time of MDA attainment in early and long-term PsA after starting sDMARDs in clinical practice. Methods: 253 (M/F–93/160) PsA pts according to CASPAR criteria were included in the RU-PsART, after signing consent participation forms; median (Me) age 47 [Min 20 – Max 82] years (yrs.). All patients were divided into two groups according to disease duration at time of sDMARDs initiation: early PsA ≤2 yrs. (165pts) and long-term PsA>2 yrs (88pts). All pts underwent standard clinical examinations of PsA and psoriasis activity. All pts were treated with the following sDMARDs: Oral Methotrexate (MTX) (103pts), intramuscular MTX (30pts), subcutaneous MTX (78pts), Leflunomide (7pts), Sulfasalazine (24pts), Apremilast (10pts), Tofacitinib (1pts). MDA was defined as ≥ 5 of the following criteria: tender joint count ≤1, swollen joint count ≤1, PASI≤1 or BSA≤3, patient pain global assessment VAS≤15, patient's global disease activity VAS≤20, HAQ≤0, 5, enthesitis count ≤1. The cumulative frequency and the time of MDA attainment were calculated in both groups. Kaplan-Meier cumulative analysis, Me [Min-Max], ORs with 95% CI, %, Breslow, Tarone-Ware, Log Rank tests were performed. All CI>1, p<0.05, were considered to indicate statistical significance. Results: MDA has been achieved by the use of sDMARDs treatment in 39 out of 165 (24%) pts with early PsA and in 4 out of 88 (5%) pts with long-term PsA. Early PsA pts have more chance to achieve MDA in comparison to long-term PsA pts, OR=6.5 [CI 95% 2.2-18.9]. Comparative analysis has shown that cumulative frequency of MDA achievement after sDMARDs initiation was significantly higher (42% vs 5%) and faster (21 months vs 11 yrs.) in early PsA than in long-term PsA (p<0.05 for Breslow, Tarone-Ware and Log Rank tests) (Fig. 1 ). Fig. 1. Cumulative frequency and the time of MDA achievement after starting sDMARDs in early and long-term PsA. Conclusion: Our study suggests that sDMARDs initiation (mostly MTX-monotherapy) at an early stage of PsA allows to achieve MDA significantly faster and more often than in long-term PsA. Disclosure of Interests: Elena Loginova Speakers bureau: Novartis, Celgene Corporation, Biocad, Janssen, AbbVie Inc, Tatiana Korotaeva Speakers bureau: Novartis, Celgene Corporation, AbbVie Inc, Biocad, Janssen, Pfizer, UCB, Lilly, Anastasia Koltakova: None declared, ELENA GUBAR: None declared, Yulia Korsakova Speakers bureau: Celgene Corporation, Janssen, Maria Sedunova: None declared, Igor Pristavsky: None declared, Irina Umnova: None declared, Irina Bondareva: None declared, Snezana Kudishina: None declared, Alexander Lila Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc.